Immunogenicity and Optimal Timing of 13-Valent Pneumococcal Conjugate Vaccination during Adjuvant Chemotherapy in Gastric and Colorectal Cancer: A Randomized Controlled Trial - Choi, Wonyoung; Kim, Jong Gwang; Beom, Seung-Hoon; Hwang, Jun-Eul; Shim, Hyun-Jung; Cho, Sang-Hee; Shin, Min-Ho; Jung, Sin-Ho; Chung, Ik-Joo; Song, Joon Young; Bae, Woo Kyun (Cancer research and treatment, 2020)
Pneumococcal vaccination (13-valent pneumococcal conjugate vaccine [PCV13]) is recommended to cancer patients undergoing systemic chemotherapy. However, the optimal time interval between vaccine administration and initiation of chemotherapy has been little studied in adult patients with solid malignancies. We conducted a prospective randomized controlled trial to evaluate whether administering PCV13 on the first day of chemotherapy is non-inferior to vaccinating 2 weeks prior to chemotherapy initiation. Patients were randomly assigned to two study arms, and serum samples were collected at baseline and 4 weeks after vaccination to analyze the serologic response against Streptococcus pneumoniae using a multiplexed opsonophagocytic killing assay. Of the 92 patients who underwent randomization, 43 patients in arm A (vaccination 2 weeks before chemotherapy) and 44 patients in arm B (vaccination on the first day of chemotherapy) were analyzed. Immunogenicity was assessed by geometric mean and fold-increase of post-vaccination titers, seroprotection rates (percentage of patients with post-vaccination titers > 1:64), and seroconversion rates (percentage of patients with > 4-fold increase in post-vaccination titers). Serologic responses to PCV13 did not differ significantly between the two study arms according to all three types of assessments. The overall antibody response to PCV13 is adequate in patients with gastric and colorectal cancer during adjuvant chemotherapy, and no significant difference was found when patients were vaccinated two weeks before or on the day of chemotherapy initiation.